Post-ERCP Emphysematous Cholecystitis in a Young Woman: A Rare and Potentially Fatal Complication - Roisin Stack; Joseph McLoughlin; Amy Gillis; Barbara M. Ryan (Case Reports in Gastrointestinal Medicine)
A 45-year-old woman with suspected Functional Biliary Sphincter Disorder (FBSD) developed Clostridium perfringens related emphysematous cholecystitis after ERCP. A low index of suspicion for emphysematous cholecystitis in this young, otherwise healthy woman led to a significant delay in making the correct diagnosis, and air in the gallbladder was wrongly attributed to a possible gallbladder perforation. ERCP is associated with significant risks, particularly in patients with FBSD, where diagnostic uncertainty renders the balance of risk versus benefit even more critical. Post-ERCP emphysematous cholecystitis secondary to Clostridium perfringens is a rare but potentially fatal complication.